The effect of thymus vulgaris l. oil as growth promoter in broilers - Ciftci, Mehmet; Guler, Talat; Gulcihani Simsek, U.; Nihat Ertas, O.; Dalkilic, Bestami; Bicer, Zulfu (My University, 2009)
In this study, the effect of dietary antibiotic (avilamycin) and thyme oil supplementation with a standard diet at 100, 200 or 400 ppm on feed intake, daily live weight gain and feed conversion ratio in broilers were investigated. The feed intake was similar among the groups except thyme oil 400 ppm which depressed (P<0.05). The birds fed the diet containing 200 ppm thyme oil and antibiotic had the highest average daily gain, followed by those other treatment diets and control (P<0.05). From 1 to 40 days of age, feed conversation ratios were improved significantly by the supplementation with 200 ppm thyme oil and antibiotic diets (P<0.05). The supplementation of 200 ppm thyme oil and antibiotic increased daily live weight gain by 8.20, 7.40% and improved feed conversion ratio by 7.45,6.83% compared to the, control group, respectively. According to this result, 200 ppm supplementation of thyme oil to diets could be considered as an alternative natural growth promoter for poultry instead of antibiotics.
Keywords: Aves; Thymus vulgaris